Parasitism-induced changes in microbial eukaryotes of Peruvian alpaca gastrointestinal tract - Sanchez, Diana (2024)
Alpacas, important genetic resources in the Andean region of Peru, are vulnerable to diarrhea caused by pathogenic parasites such as Eimeria lamae and Giardia sp., which can be fatal, especially in neonates, due to their physiological immaturity and limited adaptability. The study investigated the diversity and abundance of intestinal fungi and protists in alpacas infected with Eimeria lamae and Giardia sp. compared to healthy alpacas. A total of 19 alpacas, aged between one and two months, were included. They were divided into two groups, one with pathological conditions (nine) and the other healthy (ten). Parasitological analyses for the detection of parasites and subsequent molecular analysis were performed on the collected fecal samples. The results revealed a greater diversity and abundance of protists in infected alpacas in comparison with healthy alpacas, while the fungal composition did not show significant changes. Therefore, parasitic infections affect the protist component of the alpaca gut microbiota. Also, it was observed that Blastocystis was identified in all healthy alpacas, serving as a possible marker of the health of the intestinal microbiota; in addition, Prussia and Pichia are beneficial fungi that help control diseases. This groundbreaking study in neonatal alpacas is the first to explore potential changes in the intestinal microbiota during an infectious state, underscoring the importance of further research to comprehend its effects on alpaca health and immune responses.